Efficacy and safety of fermented Prunus mume vinegar on fatigue improvement in adults with unexplained fatigue: A randomized controlled trial - Choi, Jung In; Lee, Ye Li; Lee, Sang Yeoup (Frontiers in Nutrition, 2022)
Backgroud: The accumulation of fatigue leads to reduced physical, emotional, psychological, and social functions. Objectives: Fermented Prunus mume vinegar (PV) improves fatigue in animals; however, studies in humans have not been conducted. We aimed to examine the effects and safety of consuming fermented PV for 8 weeks on fatigue indices in adults with unexplained fatigue while considering the placebo effect. Methods: A randomized, double-blind, placebo-controlled trial was conducted in adults of >19 years, who were diagnosed with unexplained fatigue for at least 1 month. Eighty participants were randomly assigned to receive daily 70 mL of fermented PV (2.56 mg/g, chlorogenic acid, and 15.3 mg/g, citric acid) or a placebo for 8 weeks. At baseline and 4 and 8 weeks after treatment, the participants were visited for blood tests [liver enzyme, glucose, creatinine, lactate, malondialdehyde (MDA), and creatine kinase (CK)] and questionnaires [Fatigue Severity Scale (FSS), fatigue visual analog scale (VAS), Beck Depression Inventory (BDI), the Korean version of the Brief Encounter Psychosocial Instrument (BEPSI-K), EQ-5D-3L, and EQ-VAS)]. Results: Fermented PV supplementation for 8 weeks did not remarkably improve the fatigue indices when compared to placebo. Additionally, differences in fatigue VAS, BDI, BEPSI-K, EQ-5D-3L, EQ-VAS, lactate, CK, and MDA concentrations between the groups were not observed. However, FSS had positively correlated with fatigue VAS, BDI, and BEPSI-K, whereas it was negatively correlated with EQ-5D-3L and EQ-VAS at the baseline and 8 weeks. None of the participants reported adverse events. Conclusion: The efficacy of fermented PV did not exceed the efficacy of placebo in adults with unexplained fatigue. Clinical Trial Registration: ClinicalTrials.gov, identifier: NCT04319692.